MCM-41-supported ruthenium carbonyl cluster-derived catalysts for asymmetric hydrogenation reactions - Indra, Arindam; Basu, Susmit; Kulkarni, Dhanashree G.; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Applied Catalysis A-General, 2008)
{The anionic ruthenium carbonyl cluster [Ru-4(mu-H)(3)(CO)(12)](-) has been ion-paired with (3-chloropropyl)-trimethoxysilyl-cinchonidium or sparteinium groups chemically bound to the surfaces of MCM-41 [(MCM-41-)(-O)(3)SiCH2CH2CH2NR3+Cl-
Keywords: asymmetric catalysis; functionalized MCM-41; hydrogenation catalysts; nanocatalyst; ruthenium carbonyl cluster

Potential- and time-dependent dynamic nature of an oxide-derived pdin nanocatalyst during electrochemical CO2 reduction - Bagchi, Debabrata; Sarkar, Shreya; Singh, Ashutosh Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (ACS Nano, 2022)
Electrochemical reduction of CO2 into valuable fuels and chemicals is a promising route of replacing fossil fuels by reducing CO2 emissions and minimizing its adverse effects on the climate. Tremendous efforts have been carried out for designing efficient catalyst materials to selectively produce the desired product in high yield from CO2 by the electrochemical process. In this work, a strategy is reported to enhance the electrochemical CO2 reduction reaction (ECO2RR) by constructing an interface between a metal-based alloy (PdIn) nanoparticle and an oxide (In2O3), which was synthesized by a facile solution method. The oxide-derived PdIn surface has shown excellent eCO(2)RR activity and enhanced CO selectivity with a Faradaic efficiency (FE) of 92.13% at -0.9 V (vs RHE). On the other hand, surface PdO formation due to charge transfer on the bare PdIn alloy reduces the CO2RR activity. With the support of in situ (EXAFS and IR) and ex situ (XPS, Raman) spectroscopic techniques, the optimum presence of the Pd-In-O interface has been identified as a crucial parameter for enhancing eCO(2)RR toward CO in a reducing atmosphere. The influence of eCO(2)RR duration is reported to affect the overall performance by switching the product selectivity from H-2 (from water reduction) to CO (from eCO(2)RR) on the oxide-derived alloy surface. This work also succeeded in the multifold enhancement of the current density by employing the gas diffusion electrode (GDE) and optimizing its process parameters in a flow cell configuration.
Keywords: CO2 reduction; Electrochemistry; heterostructure interface; in situ mechanism; nanocatalyst

Remarkable SO2 and H2S resistant ability on CO oxidation by unique Pd/WO3 3D hollow sphere nanocatalyst: correlating structure-activity relationships on SO2 exposure - Jeyavani, Vijayakrishnan; Kondhekar, Deepali; Bhati, Meema; Dev, Sahil; Joshi, Kavita; Devi, R. Nandini; Mukherjee, Shatabdi Porel (ACS Applied Energy Materials, 2024)
We report a simple inorganic route for synthesizing a Pd/WO3 3D hollow sphere nanocatalyst, where Pd nanoparticles are encapsulated and well distributed on porous tungsten oxide nanospheres. The synthesis protocol has advantages, as it requires no surfactant or stabilizing agent, Pd loading is easily tuned, and the as-synthesized nanomaterials can be directly used as catalysts for the CO oxidation reaction. The synthesized nanocatalyst exhibited 100% CO to CO2 conversion efficiency at 260 degrees C. In addition, the nanocatalyst demonstrated remarkable SO2 (3 ppm) tolerance during the CO oxidation reaction for prolonged SO2 sulfation of 1-21 h at 260-400 degrees C. This represents the longest SO2 exposure time reported to date based on a single metal Pd/support-based nanocatalyst. No decrement in CO conversion efficiency was observed even after SO2 (3 ppm) treatment for 21 h for the first time based on a single metal Pd-based nanocatalyst. Moreover, the synthesized nanocatalyst shows H2S (4 ppm), even in situ H2S tolerance during the CO oxidation reaction at 260 degrees C for 1-3 h and exhibited less sensitivity to prolonged and stringent sulfur exposure, with the highest H2S concentration and maximum 100% CO to CO2 conversion efficiency obtained after H2S treatment for the first time based on a Pd-based nanocatalyst to the best of our knowledge. The composition and structure of the R-Pd/WO3 nanocatalyst were not much influenced, even after the prolonged SO2 and H2S exposure during the CO oxidation reaction, as verified from spent catalyst analysis. Finally, our DFT-based model provides insights into understanding the observed sulfur resistance on Pd/WO3 by analyzing the underlying electronic structure. Therefore, our strategic synthesis methodology will open up many opportunities to select Pd/metal oxide-based nanomaterials for designing highly efficient, stable, and SO2/H2S-resistant nanocomposite catalyst.
Keywords: CO oxidation; DFT calculation; nanocatalyst; palladium (Pd); SO2 andH(2)S resistant ability; structure-activityrelationships; tungstenoxide (WO3)